Management of Marine and Fisheries Resources: Cipta Kerja act and Islamic Perspective - Achmad Fachruddin Syah (Islamic Research, 2021)
The Tenaga Kerja act has been passed. One of the sectors associated with the Tenaga Kerja act is marine and fisheries sector. Therefore, it is important to understand the potential impact of the act on the maritime and fisheries sector. The purpose of this paper was to analyze the potential effect of the Tenaga Kerja act on the marine and fisheries sector. In addition, this paper also offers a new paradigm in optimal and environmentally friendly marine and fisheries resource management based on Islam. We used descriptive analysis method by comparing the Tenaga Kerja act with acts relating to the maritime and fisheries sector. In addition, to understand how Islam manages existing natural resources, the Koran and the Sunnah of the Prophet Muhammad Shallallahu ‘Alaihi Wa Sallam were used. The results showed that the Tenaga Kerja act opens opportunities for foreigners to exploit marine and fishery resources in Indonesia waters. As a consequence, the interests of the national fishing industry are threatened. In addition, the act created a very strong centralization of authority to the Central Government and weakened the roles of the Technical Ministers and local governments. On the other hand, Islam provides solutions in optimal management of marine and fisheries resources while maintaining their sustainability. Therefore, it is very important to consider Islam in environmental management such as in the marine and fisheries sector.